Developing a theoretical foundation to change road user behavior and improve traffic safety: Driving under the influence of cannabis (DUIC). (19th May 2018) - Ward, Nicholas J.; Schell, William; Kelley-Baker, Tara; Otto, Jay; Finley, Kari
ABSTRACT: Objectives : This study explored a theoretical model to assess the influence of culture on willingness and intention to drive under the influence of cannabis (DUIC). This model is expected to guide the design of strategies to change future DUIC behavior in road users. Methods : This study used a survey methodology to obtain a nationally representative sample ( n = 941) from the AmeriSpeak Panel. Survey items were designed to measure aspects of a proposed definition of traffic safety culture and a predictive model of its relationship to DUIC. Results : Although the percentage of reported past DUIC behaviors was relatively low (8.5%), this behavior is still a significant public health issue—especially for younger drivers (18–29 years), who reported more DUIC than expected. Findings suggest that specific cultural components (attitudes, norms) reliably predict past DUIC behavior, general DUIC willingness, and future DUIC intention. Most DUIC behavior appears to be deliberate, related significantly to willingness and intention. Intention and willingness both appear to fully moderate the relationship between traffic safety culture and DUIC behavior. Conclusions : This study explored a theoretical model to understand road user behavior involving drug (cannabis)-impaired driving as a significant risk factor for traffic safety. By understanding the cultural factors that increase DUIC behavior, we can create strategies to transform this culture and sustain safer road user behavior.